Psychopathologic risk assessment and self-esteem in patients undergoing hypospadias surgery - A. Marte; L. Pintozzi; M. Prezioso; M. Borrelli; S. Pisano (PAGEPress Publications, 2014)
Aims: Although the long-term outcomes of hypospadias surgery are considered important for psychosexual development, only a few attempts have been made to evaluate patient psico-pathology. Material and Methods: 20 out 40 patients who received under sealed cover two envelopes - the first containing the assessment tools, the other empty and prepaid for the answer - joined the study. The results came from the analysis of anamnestic interview specially created in order to gather information on how to access to surgery and the degree of information that the parents had from the surgeon, from the analysis of the CBCL (Child Behavior CheckList 2001:4-16 years) and TMA (Multidimensional self-esteem Test: the Italian version of the MSCS Multidimensional Self-Concept Scale). Of the 20 patients recruited, 15, aged from 9 to 18 years (mean age 12.5), age at operation between 2 and 5 years (mean age 3.3 yrs), have returned the questionnaires correctly compiled. Patient data were compared with those of a control group not suffering from genital pathology. Results: From the CBCL: the area of the identification of the problems showed no significant differences between the study group and the control. The area of competence, altered in both groups, did not show statistically significant differences. From the analysis of TMA: there were no statistically significant differences between the two groups in sub-domains: Social, Competence, Affect, Family and Physical. Within the subdomain school the two groups differed significantly for low self-esteem in the group of surgical patients. Conclusion: The MST test indicate that hypospadias surgery does not change the global self-esteem but, surprisingly, at least in this patient population, only a lower self-esteem in school performance in the age group considered . This study may indicate the importance of psychological support during the transition from adolescence to adulthood.